Peran Kepribadian Concientiousness dengan Kebermaknaan Hidup Warga Binaan Residivis - Armiyati (Psikodinamika: Jurnal Literasi Psikologi, 2023)
Recidivists who are undergoing coaching experience several changes in their personality, this allows them to realize mistakes, control their attitudes and actions, and have better life goals. The purpose of this study was to determine the relationship between conscientiousness personality and the meaningfulness of life for recidivist inmates at Class IIA Martapura Women's Penitentiary. The method used in this research is quantitative research with a correlational approach. Sampling used in this research is total sampling. The subjects of this study were 84 recidivist at Class IIA Martapura Women's Penitentiary. The scale used in this study is the conscientiousness personality scale and the meaningfulness of life scale, with the scaling model being the Likert scale. The results of this study indicate that there is a positive relationship between conscientiousness personality and the meaningfulness of life